Tindak Tutur Ekspresif dalam Novel Berbahasa Minangkabau Rindu Banda Sapuluah Karya Ermanto Tolantang: Metode Linguistik Korpus - Silvia Ananda Putri; Ermanto (Universitas Negeri Padang, 2024)
This study aims to explain two main points of discussion, namely (1) types of expressive speech acts in the Minangkabau language novel Rindu Banda Sapuluah by Ermanto Tolantang and (2) expressive speech strategies in the Minangkabau language novel Rindu Banda Sapuluah by Ermanto Tolantang. This research uses qualitative research with descriptive method. The data in this study were obtained from the utterances containing expressive speech acts in the Minangkabau novel Rindu Banda Sapuluah by Ermanto Tolantang. Data collection techniques use documentation techniques with written sources, namely the Minangkabau language novel Rindu Banda Sapuluah by Ermanto Tolantang in the form of documents as a place for data collection, assisted by the corpus linguistics application KORTARA (Korpus Nusantara). The results showed that (1) there are twelve types of expressive speech acts, including joy, criticism, hatred, pleasure, misery, thanking, congratulating, apologizing, complaining, criticizing, praising, and expressing condolences and (2) five expressive speech strategies, including speaking frankly without pleasantries, speaking frankly with positive politeness, speaking frankly with negative politeness, speaking vaguely, and speaking silently. The most dominant type of expressive speech act used is the expressive speech act of complaining and the most dominant speech strategy used is the strategy of speaking frankly without pleasantries.